2022
DOI: 10.3390/v14040762
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Pattern of Norovirus Dispersal in an Oyster Growing Region in the Northeast Pacific

Abstract: Contamination of Pacific oysters, Crassostrea gigas, by human norovirus (HuNoV) is a major constraint to sustainable shellfish farming in coastal waters of the Northeast Pacific. HuNoV is not a marine virus and must originate from a human source. A barrier to effective management is a paucity of data regarding HuNoV dispersal in the marine environment. The main objective of this study was to identify the spatial distribution and persistence of HuNoV in an active shellfish farming region in the Northeast Pacifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Several studies in NZ and overseas have assessed the spatial and temporal distribution of norovirus in coastal environments (Brake et al, 2017 ; Campos et al, 2015 ; Green et al, 2022 ; Greening & Lewis, 2007 ; Winterbourn et al, 2016 ). Overall, these studies show that viral levels decline with distance and time from sewage sources.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in NZ and overseas have assessed the spatial and temporal distribution of norovirus in coastal environments (Brake et al, 2017 ; Campos et al, 2015 ; Green et al, 2022 ; Greening & Lewis, 2007 ; Winterbourn et al, 2016 ). Overall, these studies show that viral levels decline with distance and time from sewage sources.…”
Section: Discussionmentioning
confidence: 99%
“…For norovirus, the ISO standard (ISO 15216-1:2017) [12,13] adopted in this study provided a useful reference for evaluation of an alternative method, which was found not to differ significantly in sensitivity. Methods with standardised approaches and defined quantitative controls have recently been used in quantitating the recovery of norovirus from food, which is important in understanding the role of food and food handlers in norovirus transmission pathways [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Chassaing et al conducted a meta-analysis of publications on NoV-related foodborne outbreaks from 1993 to 2019 and found that bivalve molluscan shellfish accounted for 53% of the implicated food sources [ 12 ]. For perspective, the prevalence of NoV in oysters from other regions is reported in the range of <2% in Australia, 9% in France, 3.9 to 20% in the USA, 16.9% in China, 32.1% in Spain, and up to 71.6% in the United Kingdom [ 13 ]. Our previous research entailed a year-long investigation into oyster contamination in aquaculture farms and revealed that 16.9% (60/356) of the collected oyster samples tested positive for NoV [ 14 ].…”
Section: Introductionmentioning
confidence: 99%